2021
DOI: 10.1002/jemt.23670
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related ultrastructural characterizations of the teeth of the white grouper (Epinephelus aeneus) in the different three age‐stages

Abstract: This study represents the first attempt to describe ultrastructural features of teeth in different three ages of white grouper (Epinephelus aeneus) grossly and by the aid of the electron microscope. The current study depends on 18 oropharyngeal cavity of E. aeneus from each age-stages. There are common and special characterization between each age. Five teeth bands in the roof (incisive, canine, upper molar, palatine, and vomer), while two bands in the floor (incisive, molar). The apical teeth part resembles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 39 publications
6
25
0
Order By: Relevance
“…The buccal cavity of fish plays an important role in prey capture and food transportation and help in the fish adaptation to the surrounding environmental conditions (Alexander, 1967; Alsafy et al, 2021; Cataldi et al, 1987; El‐Gendy, Alsafy, & Tanekhy, 2016; Elshoud‐Oldenhave & Osse, 1976). Previously, the oropharyngeal cavity was described by the SEM investigations in the different feeding habits fish‐species; carnivorous species (Alsafy et al, 2021; Bishop & Odense, 1966; Cataldi et al, 1987); plankton feeder species, (Chakrabarti & Sinha, 1987; Nandi & Saikia, 2021; Sinha & Chakrabarti, 1985), herbivorous species (Atkinson & Collin, 2012; El Bakary, 2011; El Bakary, 2012; Yashpal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The buccal cavity of fish plays an important role in prey capture and food transportation and help in the fish adaptation to the surrounding environmental conditions (Alexander, 1967; Alsafy et al, 2021; Cataldi et al, 1987; El‐Gendy, Alsafy, & Tanekhy, 2016; Elshoud‐Oldenhave & Osse, 1976). Previously, the oropharyngeal cavity was described by the SEM investigations in the different feeding habits fish‐species; carnivorous species (Alsafy et al, 2021; Bishop & Odense, 1966; Cataldi et al, 1987); plankton feeder species, (Chakrabarti & Sinha, 1987; Nandi & Saikia, 2021; Sinha & Chakrabarti, 1985), herbivorous species (Atkinson & Collin, 2012; El Bakary, 2011; El Bakary, 2012; Yashpal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The current work observed that the buccal cavity of the grey gurnard was symmetrical, wide. There are some minor morphological variations in the opening of the buccal cavity between the different fish‐species of the different feeding habits; the carnivorous fish had a wide semilunar opening of the buccal cavity such as white grouper Epinephelus aeneus , gilthead seabream Sparus aurata , and Bagrus Bayad (Alsafy et al, 2021; Alsafy, Bassuoni, & Hanafy, 2018; El Bakary, 2012; El‐Gendy et al, 2016), and in omnivorous fish as in Clarias gariepinus (Gamal, Elsheikh, & Nasr, 2012). While, the wide topsy‐turvy with anteriorly protrusible sub‐terminal mouth observed in the flatfish common solea, but the flat oral cavity observed in elasmobranch A. rostrata (Atkinson & Collin, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations